Effect of S-adenosylmethionine on liver regeneration induced by partial hepatectomy - Kohoutek, Lukás; Cervinková, Zuzana; Kucera, Otto; Rousar, Tomás; Garnol, Tomás; Siller, Jirí; Lotková, Halka (General physiology and biophysics, 2010)
S-adenosylmethionine (SAMe) is a key metabolite regulating growth, differentiation and death of hepatocytes. Experimentally, exogenous SAMe has been documented to attenuate hepatocarcinogenesis. The aim of our study was to evaluate the effect of SAMe on proliferation of hepatocytes that are not cancerously transformed. Partial 2/3 hepatectomy (PH) was performed in rats, control animals underwent laparotomy. SAMe was injected immediately after the surgery and then at 24 h intervals for two days at 10 or 40 mg/kg. The animals were sacrificed 24, 48 and 72 h after operation and the intensity of liver regeneration was evaluated. SAMe treatment at 10 mg/kg was associated with decrease in the synthesis of liver DNA 48 h after PH, however, it was not reflected in DNA content. SAMe treatment at 40 mg/kg led to the reduction of DNA synthesis 72 h after PH followed by the diminution of DNA content. The results have documented the inhibition of the liver regeneration by SAMe that may be mediated by the suppression of liver fat accumulation. Cell GSH level correlating with the growth rate was not affected by SAMe. Prevention from the decrease in the intracellular content of SAMe, as a factor attenuating regeneration remains to be verified.
Keywords: potkani Wistar; játra; S-Adenosylmethionine; Rats; hepatektomie; Animals; Hepatectomy; krysa rodu Rattus; Liver; mužské pohlaví; Liver Regeneration; Male; Rats, Wistar; zvířata; regenerace jater; S-adenosylmethionin